Penggunaan Kontras Warna dalam Fotografi - Felix, John (Bina Nusantara University, 2010)
Photography now is a science that attract many people from those who learn it jus for hobby or those who wish to enter the industry. Since human found a way to record colors in photographic meaning, photographers face a new challenge on how to compose colors and what is the effect of using the chosen color. This article explain how to apply colors not just as a way to make a photograph looks as what human sees but also as a visual element to give an emphasis to the main subject and still looks comfortable to the eye of the viewer.